Old Testament Preaching from the Lectionary Challenge, Case Study, and Reflection - Callaham, Scott N. (2013)
This article reflects upon preaching Old Testament texts from the Revised Common Lectionary in light of a recent three-year experiment of favoring the Old Testament readings for sermon development. Old Testament texts in the lectionary experience re-contextualization due to their appropriation as supporting material for the Synoptic Gospel readings and the metanarrative of the “church year.” Countering the resulting transformation or loss of meaning calls for attention to canonical context, including the trajectory that Old Testament texts themselves set toward New Testament themes.
Keywords: Bible. Gospels; Bible. Old Testament; biblical preaching; LECTIONARY preaching; Old Testament preaching; Preaching; re-contextualization; Revised Common Lectionary; SERMON (Literary form)